2003
DOI: 10.1177/145749690309200312
|View full text |Cite
|
Sign up to set email alerts
|

New Bone Formation Induced by Injection of Native Reindeer Bone Morphogenetic Protein Extract

Abstract: Our results suggest that BMP can be administered percutaneously, and that collagen and physiological saline are equally good carriers of injectable implants of native reindeer BMP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
2
9
1
Order By: Relevance
“…The 10 mg of bone extract group had significantly higher mean stiffness than the collagen group [9]. Our results confirm previous results, which showed that reindeer bone extract has good osteoconductivity both in [5,6,9]. It is known that the animal and fracture models, delivery systems and route of administration influence the dose response in bone healing studies [16].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The 10 mg of bone extract group had significantly higher mean stiffness than the collagen group [9]. Our results confirm previous results, which showed that reindeer bone extract has good osteoconductivity both in [5,6,9]. It is known that the animal and fracture models, delivery systems and route of administration influence the dose response in bone healing studies [16].…”
Section: Discussionsupporting
confidence: 81%
“…We have shown previously that bone extract purified from reindeer bones effectively induces ectopic new bone formation (BF) in vivo [5,6]. The native reindeer bone extract has proved to possess better osteoinductivity than bovine or ostrich bone extracts, and it has been suggested that this is due to the fact that reindeers renew their antlers annually [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, studies aiming at safe and effective products from native BMPs are still needed. We have shown previously that reindeer BMP extracts effectively induce ectopic new bone formation in vivo (Pekkarinen et al 2003(Pekkarinen et al , 2004(Pekkarinen et al , 2005a. However, the bone healing properties of reindeer BMP extract have not yet been evaluated.…”
mentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs) stimulate regeneration of bone and cartilage (Jortikka et al 1993a,b, Cook 1999, Govender et al 2002, Wozney 2002, Cheng et al 2003, Pekkarinen et al 2003. The bone-healing properties of different recombinant and extracted BMPs have been studied using long bone defect models in rabbits (Hollinger et al 1998, Kokubo et al 2003, dogs Johnson 2000, Tuominen et al 2000), rats (Takagi and Urist 1982, Chen et al 2002, Matsuo et al 2003 and sheep (Gao et al , 1997.…”
mentioning
confidence: 99%